Is Warm or Cold Calafiore Blood Cardioplegia Better? Hemodynamic, Metabolic, and Electron Microscopic Differences - Böning, Andreas; Hagmüller, Stephanie; Heep, Martina; Rohrbach, Susanne; Niemann, Bernd; Mühlfeld, Christian (The Thoracic and Cardiovascular Surgeon, 2014)
Background Controversy exists as to whether warm or cold Calafiore blood cardioplegia (BCP) is better for cardiac preservation. Therefore, we compared hemodynamic performance, myocardial metabolism, and ultrastructural preservation in rat hearts after application of cold or warm BCP.Materials and Methods The hearts of 24 male Wistar rats were excised and inserted into a blood perfused isolated heart apparatus, and after a stabilization period of 30 minutes, either cold (4°C) or warm (36°C) Calafiore BCP was administered during an aortic clamping time of 90 minutes (12 rats each). Hearts clamped without BCP and hearts immediately excised in anesthesia served as worst case and no damage controls, respectively (n = 3 each). During reperfusion, functional hemodynamic parameters were recorded in BCP groups, and myocardial oxygen consumption and lactate production were calculated. After perfusion fixation, the hearts of three rats in each group were investigated for cellular edema and mitochondrial damage by morphometry using transmission electron microscopy.Results Cardiac function after BCP application during aortic clamping showed a slightly better recovery with warm than with cold Calafiore BCP as indicated by higher left ventricular developed pressure (warm 97% of baseline, cold 68% of baseline) after warm BCP. Other hemodynamic parameters and coronary flow were not different between warm and cold BCP. Myocardial oxygen consumption and lactate production were similar under warm and cold conditions. Electron microscopy showed typical signs of ischemia in the ischemia group without BCP. Mitochondrial ultrastructure was well preserved in both BCP groups, but cellular edema was more pronounced with cold than with warm BCP. The qualitative analysis was confirmed by the morphometric cellular edema index and the volume-to-surface ratio of the mitochondria.Conclusion Only mild differences were observed between warm and cold BCP in rats with respect to cardiac function, metabolism, and tissue preservation after aortic clamping. However, a small tendency toward better postischemic recovery was observed with warm BCP.
Keywords: cardiopulmonary bypass; ischemia/reperfusion; myocardial protection/cardioplegia (incl. metabolism); tissue preservation